Enhancing mechanical and flame retardant characteristics of glass fiber-epoxy laminated composites through MXene and functionalized-MXene integration - Yilmaz, Ayten Nur Yuksel; Bedeloglu, Ayse Celik; Yunus, Doruk Erdem (Elsevier, 2024)
MXene, a 2D transition metal carbide and nitride with graphene-like layered structures, has become one of the preferred choice for nano-reinforcement in polymer matrix composites in recent years due to its outstanding properties such as specific surface area, excellent thermal and mechanical characteristics, and high conductivity. In this study, the glass fiber-epoxy laminated composites reinforced with Ti3C2Tx-MXene (M)/ functionalizedMXene (FM) were produced using the hand lay-up procedure followed by vacuum bagging process. The effects of varying filler amounts (0.125, 0.25, 0.375, and 0.5%) on the mechanical and flame retardancy properties of glass fiber-epoxy composites were examined. In both M and FM reinforced composites, the highest values of mechanical strengths were obtained with a 0.25% filler, while a decrease in mechanical strengths was observed beyond this reinforcement amount. The 0.25 wt% FM-reinforced composite exhibited 19.21%, 27.55%, and 12.40% higher tensile, flexural, and interlaminar shear strengths (ILSS) than the pristine glass fiber-epoxy composite (N-C). Post-test analysis revealed the presence of matrix cracks, fiber breakage, and fiber pull-out damages were observed on the surfaces of composite samples. The flame retardant properties of the composites were enhanced with the addition of MXene reinforcement, and 0.5FM-C exhibited 25.50% lower burning rate than N-C.
Keywords: Glass fibers; Polymer-matrix composites; Mechanical properties; Surface treatments